HUBUNGAN FREKUENSI MELIHAT PORNOGRAFI DENGAN SIKAP TERHADAP SEKS BEBAS PADA REMAJA KELAS X DI SMAN 1 KALITIDU KABUPATEN BOJONEGORO: HUBUNGAN FREKUENSI MELIHAT PORNOGRAFI DENGAN SIKAP TERHADAP SEKS BEBAS PADA REMAJA KELAS X DI SMAN 1 KALITIDU KABUPATEN BOJONEGORO - Megawati, Indah (WELL BEING, 2017)
Adolescence is a transition from children to adult and during this period of their life is still full of fluctuation. Not a few of them actually misbehaving and some of them stuck to free sex. Sexual attitudes of the teenagers can be influenced by several factors, including the media. The purpose of this study is to know the Relationship of Frequency Seeing Pornography with Attitude to Free Sex for Teenagers in Class X SMAN 1 KALITIDU BOJONEGORO District. In this study, researcher used a cross-sectional design with spearmen rank test using SPSS 16. Most of the population as many as 162 with a sample of 24 respondents and cluster random sampling technique in which the sample is X class of SMAN 1 KALITIDU BOJONEGORO District. The results showed that frequency of most of respondent in seeing pornography is often did it. As many as 11 respondents (45.8%), attitudes of respondents to the free sex most of them strongly agreed with the promiscuity as many as 11 respondents (45.8%), obtained p = 0000, where p <0.05 so that H1 accepted that means there is a relationship of frequency seeing pornography with attitude to free sex for teenagers with correlation coefficient value of rho = 0.901 very strong. In this case the frequency of seeing pornography affect to respondents' attitudes to free sex, but there are other factors that can affect the attitudes to free sex in this which in this study can’t be controlled, such as culture, resources, seriousness in worshiping, emotional factors.